2021
DOI: 10.1049/rpg2.12359
|View full text |Cite
|
Sign up to set email alerts
|

An effective model parameter estimation of PEMFCs using GWO algorithm and its variants

Abstract: This paper introduces the application of the variants of the Grey Wolf Optimisation algorithm for the sake of assessing unknown parameters of Proton Exchange Membrane Fuel Cells models. Three versions of Grey Wolf Optimisation algorithm are applied: Conventional Grey Wolf Optimisation, Improved Grey Wolf Optimisation based on dimension learning-based hunting, and Selective Opposition-based Grey Wolf Optimisation. Moreover, Optimisation algorithms of Ant Lion Optimiser, Atom search optimisation, Dragonfly algor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…DLH search strategy improves the balance between local search and global search and keeps the diversity of population. In recent applied studies (Diab et al, 2022, Yesilbudark, 2021, Sales et al, 2021, IGWO's superiority in solving practical problems has been demonstrated. IGWO mainly consists of three stages: initialization (Step1), move (Step2), and select and update (Step3).…”
Section: Weight Optimization Algorithmmentioning
confidence: 99%
“…DLH search strategy improves the balance between local search and global search and keeps the diversity of population. In recent applied studies (Diab et al, 2022, Yesilbudark, 2021, Sales et al, 2021, IGWO's superiority in solving practical problems has been demonstrated. IGWO mainly consists of three stages: initialization (Step1), move (Step2), and select and update (Step3).…”
Section: Weight Optimization Algorithmmentioning
confidence: 99%
“…PEMFC parameter estimation was done by developing Black Widow Optimization (BWO) along with the comparison of its results with other different meta-heuristic algorithms under various operating temperatures. Various other meta-heuristic algorithms that have been developed are the Slime Mould (SM)-based optimization algorithm, Modified Monarch Butterfly Optimization (MMBO) algorithm, Backtracking Search Algorithm combined with Burger's Chaotic map (BSABCM), Particle Swarm Optimization (PSO) [15], Genetic Algorithms (GA) [16], Chaotic Mayflies Optimization (CMO) algorithm [17], Grey Wolf Optimizer (GWO) [18], Whale Optimization Approach (WOA) [19], Salp Swarm Optimization algorithm (SSOA) [20], Effective Informed Adaptive PSO (EIA-PSO) [21], Cuckoo Search-Ant Colony Optimization (CS-ACO) [22], bi-inspired algorithm [23], Tribe PSO Algorithm (T-PSO) [24], Bi-Subgroup Optimization (BSO) [25], Sine Cosine Algorithm (SCA) [26], and Modified Owl Search Algorithm (DOSA) [27]. Another meta-heuristic algorithm, for example Puffer Fish (PF) [28], based on the behavior of male puffer fish in order to charm the female puffer fish by building special circular structures on the seabed, was developed for finding the optimal solution set to the problems of optimization.…”
Section: Introductionmentioning
confidence: 99%
“…Centroid opposition integrated with multiple strategies embedded on salp swarm algorithm can reduce the probability of the failure design system of reliability optimization [38]. An improved grey wolf optimizer with selective opposition shows efficiency for solving proton exchange membrane fuel cells 250W-stack [39]. The dynamic opposite generates mutual learning which is integrated with the mutation strategy for solving multi-task optimization problems [40].…”
Section: Introductionmentioning
confidence: 99%